2010
DOI: 10.1177/0148607109338215
|View full text |Cite
|
Sign up to set email alerts
|

Stability of MCT/LCT‐Based Total Nutrient Admixtures for Neonatal Use Over 30 Hours at Room Temperature

Abstract: For neonatal TNAs, AA level is the most sensitive determinant of stability, and the PFAT5 parameter is the most sensitive indicator of stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 32 publications
(38 reference statements)
2
17
0
2
Order By: Relevance
“…It was ranged between 5.4 and 5.8 for three admixtures of the four. Anyway, this was reported as common in admixtures for preterm infants and this contributes to avoid calcium–phosphate precipitation since it is below the area of insoluble [CaHPO 4 ] formation 21. Our results correlate with some studies in the literature which reported that small volumes of AIO PNAs with low pH, high calcium concentration and an amino acids concentration above 2% (which is the case here) are stable.…”
Section: Discussionsupporting
confidence: 88%
“…It was ranged between 5.4 and 5.8 for three admixtures of the four. Anyway, this was reported as common in admixtures for preterm infants and this contributes to avoid calcium–phosphate precipitation since it is below the area of insoluble [CaHPO 4 ] formation 21. Our results correlate with some studies in the literature which reported that small volumes of AIO PNAs with low pH, high calcium concentration and an amino acids concentration above 2% (which is the case here) are stable.…”
Section: Discussionsupporting
confidence: 88%
“…This approach accounts only for the pH effect of the lipids, leaving other effects untested. In addition, although a simulated test of 1.5% AA plus lipids was performed, previous studies have shown lipid instability in such 3‐in‐1 admixtures containing <4% AA 18 . Our institution routinely compounds 2‐in‐1 PN with the lipids added via y‐site administration.…”
Section: Discussionmentioning
confidence: 99%
“…As the final stability of AIO compounded admixtures is also known to be affected by the composition of commercial lipid emulsions and commercial solutions of amino acids, 15 , 16 each batch of admixtures (batch 1 and batch 2) was prepared in 2 different ways using the most common commercial formulations in Greece. The first using LE1 as the lipid emulsion in combination with AA1 as the amino acid solution (batch S) and the second using LE2 as the lipid emulsion in combination with AA2 as the amino acid solution (batch C).…”
Section: Methodsmentioning
confidence: 99%